Target opportunity selling : top sales performers reveal what really works - Read, Nicholas A. C. (McGraw-Hill Education, 2014)
Reports on how top sales performers are creating and winning deals in today's highly-competitive, post-recession marketplace. Based on more than 20,000 hours of interviews and field observation, sales thought leader Nic Read reveals how modern rainmakers are beating the odds and making it look easy. At the heart of this 'sales renaissance' is the Sales Expansion Loop, a modern alternative for the 'sales funnel' that is better suited for long cycle, solution sales. The author shows how to navigate the Loop to manage large opportunities at every stage. Each chapter includes insights, anecdotes and the author's signature 'call it as he sees it' style, with practical how-tos on sales qualification, first meetings, competitive strategy, relationship management and closing. --